Sedimentary ancient DNA: a new paleogenomic tool for reconstructing the history of marine ecosystems - Nguyen, Ngoc-Loi; Devendra, Dhanushka; Szymańska, Natalia; Greco, Mattia; Angeles, Inès Barrenechea; Weiner, Agnes K. M.; Ray, Jessica Louise; Cordier, Tristan; De Schepper, Stijn; Pawłowski, Jan; Pawłowska, Joanna (Frontiers in Marine Science, 2023)
Sedimentary ancient DNA (sedaDNA) offers a novel retrospective approach to reconstructing the history of marine ecosystems over geological timescales. Until now, the biological proxies used to reconstruct paleoceanographic and paleoecological conditions were limited to organisms whose remains are preserved in the fossil record. The development of ancient DNA analysis techniques substantially expands the range of studied taxa, providing a holistic overview of past biodiversity. Future development of marine sedaDNA research is expected to dramatically improve our understanding of how the marine biota responded to changing environmental conditions. However, as an emerging approach, marine sedaDNA holds many challenges, and its ability to recover reliable past biodiversity information needs to be carefully assessed. This review aims to highlight current advances in marine sedaDNA research and to discuss potential methodological pitfalls and limitations.